2022
DOI: 10.1101/2022.02.21.481343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aberrant cortical development is driven by impaired cell cycle and translational control in aDDX3Xsyndrome model

Abstract: Mutations in the RNA helicase, DDX3X, are a leading cause of Intellectual Disability and present as DDX3X syndrome, a neurodevelopmental disorder associated with cortical malformations and autism. Yet the cellular and molecular mechanisms by which DDX3X controls cortical development are largely unknown. Here, using a mouse model of Ddx3x loss-of-function we demonstrate that DDX3X directs translational and cell cycle control of neural progenitors, which underlies precise corticogenesis. First, we show brain dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The 5′UTR of Protein Kinase A (PKA) is similar to that of RAC1, and its translation is also regulated by DDX3X, affecting neurite development ( Chen et al, 2016 ). Through ribosome profiling in a murine cortical development model, Hoye et al (2022) identified a host of DDX3X-regulated genes involved in neurological development, such as REST Corepressor 2 (Rcor2), SET Domain-Containing Protein 3 (Setd3) and DNA Topoisomerase II Binding Protein 1 (Topbp1). These multiple links to translation of mRNAs for neurodevelopmental genes may provide insights into the causes of DDX3X-associated intellectual disability (DDX3X syndrome) ( Hoye et al, 2022 ).…”
Section: Translation Regulation By Ddx3x and Its Physiological Conseq...mentioning
confidence: 99%
See 2 more Smart Citations
“…The 5′UTR of Protein Kinase A (PKA) is similar to that of RAC1, and its translation is also regulated by DDX3X, affecting neurite development ( Chen et al, 2016 ). Through ribosome profiling in a murine cortical development model, Hoye et al (2022) identified a host of DDX3X-regulated genes involved in neurological development, such as REST Corepressor 2 (Rcor2), SET Domain-Containing Protein 3 (Setd3) and DNA Topoisomerase II Binding Protein 1 (Topbp1). These multiple links to translation of mRNAs for neurodevelopmental genes may provide insights into the causes of DDX3X-associated intellectual disability (DDX3X syndrome) ( Hoye et al, 2022 ).…”
Section: Translation Regulation By Ddx3x and Its Physiological Conseq...mentioning
confidence: 99%
“…Through ribosome profiling in a murine cortical development model, Hoye et al (2022) identified a host of DDX3X-regulated genes involved in neurological development, such as REST Corepressor 2 (Rcor2), SET Domain-Containing Protein 3 (Setd3) and DNA Topoisomerase II Binding Protein 1 (Topbp1). These multiple links to translation of mRNAs for neurodevelopmental genes may provide insights into the causes of DDX3X-associated intellectual disability (DDX3X syndrome) ( Hoye et al, 2022 ). DDX3X also translationally regulates a suite of immune genes, including Transforming Growth Factor ß (TGF-ß) ( Lai et al, 2008 ), IL-8, IL-18 ( Soto-Rifo et al, 2012 ), signal transducer and activator of translation 1 (STAT1), Transforming Growth Factor-Beta-Activated Kinase 1 (TAK1), and Protein Activator of Interferon Induced Protein Kinase EIF2AK2 (PACT) ( Ku et al, 2019 ).…”
Section: Translation Regulation By Ddx3x and Its Physiological Conseq...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most DDX3X syndrome individuals are female, an observation leading to the idea that the Y-linked homolog DDX3Y can compensate for DDX3X loss and contribute to milder phenotypes in males carrying DDX3X mutations [ 171 , 172 ]. Complete loss of Ddx3x in a conditional knockout ( Ddx3x -cKO) mouse model led to microcephaly only in females, which might suggest that expression of the Y-linked homolog Ddx3y explains why Ddx3x -cKO male mice are phenotypically milder than Ddx3x -cKO females [ 173 ]. In addition, loss of one versus two Ddx3x copies caused vastly different corticogenesis phenotypes: Ddx3x -cKO females presented profound apoptosis in neural progenitors and neurons in the developing neocortex, whereas heterozygous females and Ddx3x -cKO males had impaired neurogenesis without cell death.…”
Section: X-linked Genes and Sexual Differentiation Of The Brainmentioning
confidence: 99%
“…This is partly a consequence of the generalized belief that the Y chromosome encodes just a handful of protein-coding genes only important for male reproduction along with a much larger proportion of repetitive and/or noncoding “junk” genetic material. Although some studies have recently demonstrated, as discussed in the previous section, that expression of Y homologs of X/Y gene pairs such as Uty , Ddx3y and Nlgn4y is critical during brain development in males [ 117 , 133 , 173 , 174 , 180 ], ensuring a two-dose autosomal-like expression for these loci in XY that matches expression levels in XX (the latter carrying two active gene copies due to XCI escape), further research addressing the specific functions of Y-encoded homologs and differences with their X-linked counterparts at developmental and physiological levels is required. Of note, there has been recent interest in the Y noncoding genome and its contribution to both sex determination and other traits in health and disease [ 181 ].…”
Section: Y-linked Genes and Sexual Differentiation Of The Brainmentioning
confidence: 99%